Multilateral Approaches to the Back-end of the Nuclear Fuel Cycle: Challenges and Possibilities - 류호진1; Ho Jin Ryu (Journal of nuclear fuel cycle and waste technology (Online), 2010)
원자력의 중흥기를 맞이하여 민감한 핵연료주기 기술의 무분별한 확장을 억제하고자 다양한 핵연료주 기 다자 방안이 제시되고 있다. 현재 원자력 공급국 위주의 핵연료주기 다자화가 추진되고 있는 실정에서 후행 핵연료주기 기술의 다자화 추진 추이를 파악하고자 사용후핵연료 공동 관리 시설에 대한 분석 결과 를 검토하였다. 또한 후행 핵연료주기 연구개발 시설의 다자화를 제안하고 기대효과와 문제점을 검토한 후 이를 실현하기 위한 추진방안을 도출하였다. Various multilateral approaches to the nuclear fuel cycle have been proposed in order to suppress the expansion of sensitive fuel cycle technology. In order to prepare for the future multilaterallization of the nuclear fuel cycle, existing multilateral spent fuel management programs are analyzed. A trial multilateralization of a domestic R&D facility for the back end of the nuclear fuel cycle is proposed and its challenges, possibilities and implementation strategy are discussed.